Therapeutic Music Creation Based on Soundscape of North Sumatra as a Media for Relaxation amid the Covid-19 Pandemic - Herna Hirza; Wiflihani Wiflihani; Ifwanul Hakim; Mukhlis Mukhlis; Suharyanto Suharyanto (Budapest International Research and Critics University, 2020)
One of the effects of the Covid-19 pandemic on humans is a disturbance in the psychological aspect. This study offers music therapy based on the soundscape of North Sumatra as an alternative to balance emotional turmoil amid the new life adaptation of the Covid-19 pandemic. Soundscape is defined as sound or sounds that come from nature (natural sound). The method used in this research is a qualitative approach. The data was collected through audio recording of soundscapes in various regions in North Sumatra, from mountains to coastal areas, which were later combined with sounds from traditional musical instruments to form a complete therapeutic music composition. The creation process includes pre-production and studio work which includes exploration, creation, editing, mixing, and mastering.